Patient Reported Outcomes in Chronic Inflammatory Diseases: Current State, Limitations and Perspectives - Tran, Florian; Schirmer, Jan Henrik; Ratjen, Ilka; Lieb, Wolfgang; Helliwell, Philip; Burisch, Johan; Schulz, Juliane; Schrinner, Florian; Jaeckel, Charlot; Müller-Ladner, Ulf; Schreiber, Stefan; Hoyer, Bimba F. (Frontiers in Immunology, 2021)
Chronic inflammatory diseases (CID) are emerging disorders which do not only affect specific organs with respective clinical symptoms but can also affect various aspects of life, such as emotional distress, anxiety, fatigue and quality of life. These facets of chronic disease are often not recognised in the therapy of CID patients. Furthermore, the symptoms and patient-reported outcomes often do not correlate well with the actual inflammatory burden. The discrepancy between patient-reported symptoms and objectively assessed disease activity can indeed be instructive for the treating physician to draw an integrative picture of an individual’s disease course. This poses a challenge for the design of novel, more comprehensive disease assessments. In this mini-review, we report on the currently available patient-reported outcomes, the unmet needs in the field of chronic inflammatory diseases and the challenges of addressing these.